ALTERNATIVE FORMS OF PRE-TRIAL SETTLEMENT OF DISPUTES ARISING FROM PUBLIC RELATIONS: FOREIGN EXPERIENCE AND PROSPECTS FOR USE IN THE REPUBLIC OF KAZAKHSTAN - Dossanova Фатима Пулатовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2018)
The study of issues of resolving public disputes using alternative methods on the example of foreign countries is due to a number of circumstances. First, Kazakhstan legislation already has experience in applying mediation in public-private relations. Secondly, at present in the sphere of public relations there are conflict situations in which there is a clash of private and public interests. Thirdly, public disputes continue to fall into one of the most difficult categories of cases, and they occupy leading positions in judicial practice. This article presents an analysis of alternative forms of resolving public conflicts with a view to possibly taking it into account when developing a domestic legal framework for resolving disputes in the field of public relations using alternative ways of traditional consideration that are successfully used in foreign countries. The study of alternative forms of settling public conflicts in foreign countries showed a variety of their legal consolidation, various options for implementation. The settling of public disputes using alternative methods is applied both in pre-trial and judicial procedures, by specialized judicial bodies, and by quasi-judicial bodies. Of all the variety of alternative forms of resolving public conflicts, the most common are two forms: direct negotiations of the parties to the dispute, involving the parties to resolve the dispute without the help of intermediaries and negotiations with the help of a mediator (mediation), suggesting the existence of a mediator and its assistance to the parties to the dispute in resolving it. Alternative forms of pre-trial or out-of-court settlement of disputes arising in the field of public relations can reduce the number of relevant proceedings in court, continue the further modernization of the existing domestic legislation on ensuring access to justice.